1980
DOI: 10.1073/pnas.77.12.7227
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the intermediary electron acceptor (pheophytin) and a possible plastoquinone-iron complex in photosystem II reaction centers

Abstract: Photoreduction of the intermediary electron acceptor, pheophytin (Pheo), in photosystem II reaction centers of spinach chloroplasts or subchloroplast particles (TSF-II and TSF-IIa) at 220 K and redox potential Eh = -450 mV produces an EPR doublet centered at g = 2.00 with a splitting of 52 G at 7 K in addition to a narrow signal attributed to Pheo (g = 2.0033, AH -13 G). The doublet is eliminated after extraction of lyophilized TSF-II with hexane containing 0. Phototrapping of Pheo-in PS II at 295 K is accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
1
6

Year Published

1981
1981
2006
2006

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(75 citation statements)
references
References 25 publications
3
65
1
6
Order By: Relevance
“…4). In fact, Co is more effective than Mn in replacing Fe in the QA-Fe-QB complex (20,22). It was suggested by Michel and Deisenhofer (33) that the Fe provides a binding site for HCO .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…4). In fact, Co is more effective than Mn in replacing Fe in the QA-Fe-QB complex (20,22). It was suggested by Michel and Deisenhofer (33) that the Fe provides a binding site for HCO .…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it is possible that Co is a better ligand than Mn for HCO3. On the other hand, it was also demonstrated that the formation of a complex between QA and Fe was required to form a stable primary acceptor complex (20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The appearance of an EPR signal at g = 2.0044, attributed to a free radical originating from the semiquinone form of the primary quinone electron acceptor [42], was interpreted as the non-heme Fe 2+ displacement or at least an alteration of the iron binding site by copper ions. It has been shown that other metal ions (Zn 2+ , Co 2+ , Ni 2+ , Cu 2+ , and Mn 2+ ) may substitute the non-heme iron reversibly, but only moderately are able to slow down the electron transfer in bacterial reaction centers [43].…”
Section: Non-heme Ironmentioning
confidence: 99%
“…Upon photoexcitation, a charge separation takes place between a special chlorophyll donor, P680 (2), and an intermediary acceptor, probably pheophytin (Ph) (3). The electron on Ph-is rapidly transferred to a quinone acceptor, Q (4), which is probably associated with a ferrous iron atom (5,6). If Q is reduced prior to illumination, the light-induced radical pair P6w'Ph-recombines.…”
mentioning
confidence: 99%